2001
DOI: 10.1111/1469-8986.3840601
|View full text |Cite
|
Sign up to set email alerts
|

The effects of competition and competitiveness on cardiovascular activity

Abstract: Cardiovascular activity was measured at resting baseline and in response to a car racing game, undertaken in competition or in cooperation with an experimenter, or individually. Competitiveness and win and goal orientations were assessed by questionnaire. Competition provoked increases in blood pressure and heart rate, and a significant shortening of the preejection period, an index of enhanced beta-adrenergic influences on the heart. The cooperation task was largely without effect, and although the solo task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…This is because the participants formed a team and took part in races together, so these factors must have given rise to a cooperative aspect. However, it has been reported that cooperative situations did not heighten HR [14,15,17], and so this aspect should not falsely strengthen the data in race conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is because the participants formed a team and took part in races together, so these factors must have given rise to a cooperative aspect. However, it has been reported that cooperative situations did not heighten HR [14,15,17], and so this aspect should not falsely strengthen the data in race conditions.…”
Section: Discussionmentioning
confidence: 93%
“…It is striking that psychophysiological studies have shown that such mental effort provokes β adrenergic sympathetic nerve activation, typically measured as increased heart rate, blood pressure, and cardiac output [11,12], although such β adrenergic activation was often accompanied by parasympathetic withdrawal [13]. For example, a laboratory study using a motorized toy racing car game task conducted by Harrison et al [14] and Veldhuijzen van Zanten et al [15] showed that heart rate during the task is higher in the competition condition than that in the solo and co-operation conditions. Thus, unless intense g-forces increase HR to a maximum level, competition induced mental stress during motor sports should increase heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…Though triggering additional effort, competition is often associated with stress (Harrison et al , 2001). Due to potential long‐term consequences (Van Egeren, 1992), these side‐effects gain importance in field settings.…”
Section: Introductionmentioning
confidence: 99%
“…For cognitive tasks, cardiovascular reactivity was often used as an indicator of general work‐related stress (Rau, 2006; Stromme, Wikeby, Blix, & Ursin, 1978; Turner & Carroll, 1985), and as an indicator of competition‐induced stress (Harrison et al , 2001; Krieger & Schulz, 1989; Van Egeren, 1979). In addition, there is no consent yet as to how competition triggers stress.…”
Section: Introductionmentioning
confidence: 99%
“…Competition is stressful (Harrison et al, 2001;Salvador, 2005), and for elite athletes, competitive stress is intensified by the career implications of success and failure, and the scrutiny under which they perform (Jordet, 2009). For an elite academy cricketer, performance scrutiny is unremitting even in training, where the athlete is compared with others for team selection under conditions of high expectation, requiring a continuous investment of substantial effort in the pursuit of successful performance.…”
mentioning
confidence: 99%